Predator-induced stress and the ecology of fear - Clinchy, Michael; Sheriff, Michael J.; Zanette, Liana Y. (Functional ecology, 2013)
1. Predator-induced stress has been used to exemplify the concept of stress for close to a century because almost everyone can imagine the terror of fleeing for one's life from a lion or a tiger. Yet, because it has been assumed to be acute and transitory, predator-induced stress has not been much studied by either comparative physiologists or population ecologists, until relatively recently. 2. The focus in biomedical research has always been on chronic stress in humans, which most comparative physiologists would agree results from 'sustained psychological stress — linked to mere thoughts' rather than 'acute physical crises' (like surviving a predator attack) or 'chronic physical challenges' (such as a shortage of food). Population ecologists have traditionally focused solely on the acute physical crisis of surviving a direct predator attack rather than whether the risk of such an attack may have a sustained effect on other demographic processes (e.g. the birth rate). 3. Demographic experiments have now demonstrated that exposure to predators or predator cues can have sustained effects that extend to affecting birth and survival in free-living animals, and a subset of these have documented associated physiological stress effects. These and similar results have prompted some authors to speak of an 'ecology of fear', but others object that 'the cognitive and emotional aspects of avoiding predation remain unknown'. 4. Recent biomedical studies on animals in the laboratory have demonstrated that exposure to predators or predator cues can induce 'sustained psychological stress' that is directly comparable to chronic stress in humans, and this has now in fact become one of the most common stressors used in studies of the animal model of post-traumatic stress disorder (PTSD). 5. We review these recent findings and suggest ways the laboratory techniques developed to measure the 'neural circuitry of fear' could be adapted for use on free-living animals in the field, in order to: (i) test whether predator risk induces 'sustained psychological stress' in wild animals, comparable to chronic stress in humans and (ii) directly investigate 'the cognitive and emotional aspects of avoiding predation' and hence the 'ecology of fear'.